THE USE OF INFORMATION COMMUNICATION TOOLS, THEIR MODELING AND OPTIMIZATION IN MEDICINE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article is about the stages of development of medicine in our country and the world, the organization of optimization of their use, and the development of new medical equipment models and practical implementation measures that meet the needs of the times.